Place, Spirituality, and Well-Being A Global and Multidisciplinary Approach - Counted, Victor; Ramkissoon, Haywantee; Captari, Laura E.; Cowden, Richard G. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book synthesizes perspectives on how 'place' is deeply intertwined with our spirituality and well-being. Split into three sections, this book brings together contributions from global scholars across a range of disciplines to unravel how the personal, social, and cultural spheres of place shape our spiritual experiences and overall well-being. It is an essential read for those interested in enriching their knowledge of the linkages between place, spirituality, and well-being, while also providing a foundation for future research on place and its intersections with both spirituality and well-being.
Chapter 1: Toward a Global and Multidisciplinary Understanding of Place, Spirituality, and Well-Being -- PERSONAL ENGAGEMENTS: SPIRITUAL TIES TO PLACE AND WELL-BEING -- Chapter 2: Worship Space Attachment as a Potential Contributor to Spiritual Growth -- Chapter 3: Place, Spirituality, and Wellness in the East and the West: Exploring Psychological Mechanisms of the Legendary Gyanganj -- Chapter 4: Where Heaven Meets Earth: Theological Reflection on Landscape, Social Ecology, Biocentric Spirituality, and Well-Being -- Chapter 5: Racial Justice Protests Create Spaces of Hope and Healing: The Racialization of Space and Trauma in Contexts of Racial Tensions -- Chapter 6: House Churches and Place Attachment: A Case Study with Iranian Christians in Scotland -- Chapter 7: Architecture, Time, and Well-Being: Toward Transcendence -- SOCIAL RESILIENCE: SPIRITUALITY AND WELL-BEING AMID ADVERSITY -- Chapter 8: Embodied Spirituality and Health Amidst Place Confinement and Disruptions During the COVID-19 Pandemic: Critical Analysis of the Literature and Development of a Conceptual Framework -- Chapter 10: Displacement, Fragmentation, and Well-Being of Ghanaian Church Leaders and Older Adult Christians During a Global Pandemic -- Chapter 11: Religious Communities and Well-Being During the COVID-19 Pandemic: A Practical Theological Consideration -- Chapter 12: The Early Church and Community Resilience in the Late Antique Levant: An Archaeological Perspective -- CULTURAL CONNECTIONS: SACRED SPACES, TOURISM, AND WELL-BEING -- Chapter 13: Managing the Sacred: Online Narratives of Well-Being in a Japanese Heritage Context -- Chapter 14: Clans and Spiritual Space: A Case Study of Guandi Temple in an Ancient Hakka Town in South China -- Chapter 15: Religious Tourism: Exploring Experiences of Spirituality, Place Attachment, and Well-Being in Zimbabwe -- Chapter 16: Healing Systems of Well-being and People-Place Interactions: Complexity, Context, and Connections.
Keywords: Spirituality; Religion and sociology; Psychology and religion; Sustainable architecture; Spirituality; Sociology of Religion; Psychology of Religion and Spirituality; Sustainable Architecture/Green Buildings